Gold nanorods induce early embryonic developmental delay and lethality in zebrafish (Danio rerio) - Mesquita, B (2017)
Due to their unique electronic and optical features, gold nanoparticles (AuNP) have received a great deal of attention for application in different fields such as catalysis, electronics, and biomedicine. The large-volume manufacturing predicted for future decades and the inevitable release of these substances into the environment necessitated an assessment of potential adverse human and ecological risks due to exposure to AuNP. Accordingly, this study aimed to examine the acute and developmental toxicity attributed to a commercial suspension of Au nanorods stabilized with cetyltrimethylammonium bromide (CTAB-AuNR) using early embryonic stages of zebrafish (Danio rerio), a well-established model in ecotoxicology. Zebrafish embryos were exposed to CTAB-AuNR (0–150 µg/L) to determine for developmental assessment until 96 hr post fertilization (hpf) and lethality. Uptake of CTAB-AuNR by embryos and nanoparticles potential to induce DNA damage was also measured at 48 and 96 hpf. Analysis of the concentration-response curves with cumulative mortality at 96 hpf revealed a median lethal concentration (LC50,96h) of 110.2 μg/L. At sublethal concentrations, CTAB-AuNR suspensions were found to produce developmental abnormalities such as tail deformities, pericardial edema, decreased body length, and delayed eye, head, and tail elongation development. Further, less than 1% of the initial concentration of CTAB-AuNR present in the exposure media was internalized by zebrafish embryos prior to (48 hpf) and after hatching (96 hpf). In addition, no marked DNA damage was detected in embryos after exposure to CTAB-AuNR. Overall, CTAB-AuNR suspensions produced lethal and sublethal effects on zebrafish embryos with possible repercussions in fitness of adult stages. However, these results foresee a low risk for fish since the observed effects occurred at concentrations above the levels expected to find in the aquatic environment.